2021
DOI: 10.1038/s41467-021-23777-7
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular contractile injection system is enriched in environmental microbes and associates with numerous toxins

Abstract: The extracellular Contractile Injection System (eCIS) is a toxin-delivery particle that evolved from a bacteriophage tail. Four eCISs have previously been shown to mediate interactions between bacteria and their invertebrate hosts. Here, we identify eCIS loci in 1,249 bacterial and archaeal genomes and reveal an enrichment of these loci in environmental microbes and their apparent absence from mammalian pathogens. We show that 13 eCIS-associated toxin genes from diverse microbes can inhibit the growth of bacte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 80 publications
1
54
0
Order By: Relevance
“…Classical T6SSs (subtypes i – iii) and R-type pyocins (eCISs) form relatively homogeneous groups of CISs. Recent bioinformatic analyses revealed an additional phylogenetic group of CISs with high abundance and diversity 16 19 . This group comprises hundreds of putative CIS gene clusters, with only a few of them being studied so far.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical T6SSs (subtypes i – iii) and R-type pyocins (eCISs) form relatively homogeneous groups of CISs. Recent bioinformatic analyses revealed an additional phylogenetic group of CISs with high abundance and diversity 16 19 . This group comprises hundreds of putative CIS gene clusters, with only a few of them being studied so far.…”
Section: Mainmentioning
confidence: 99%
“…This strain was previously co-isolated with the choanoflagellate Salpingoeca rosetta 26 and was shown to induce the formation of multicellular colonies (rosettes) of S. rosetta 27 29 . Bioinformatic analyses showed that ~69% of bacteria in the Algoriphagus genus harbour a putative CIS gene cluster 19 .…”
Section: Mainmentioning
confidence: 99%
“…Several similar so-called chaperones are also found in T4SS, although their functions are not well established ( 40 – 42 ). In the field of T6SS, which have great structure similarities with PVC and other eCIS complexes ( 43 ), several types of mechanisms have been determined in assisting the effector secretion. Tec (DUF4123) family proteins displayed essential roles for T6SS-dependent loading of the effectors ( 44 ); Eag (DUF1795) family proteins engaged in stabilizing effectors and promoting T6SS delivery through the spike ( 45 , 46 ); and a DUF2169 or DUF2875 protein has also been described as a chaperone or adaptor for T6SS substrates delivery ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another member of this group, found in a symbiont of amoebae, assembles bundles of T6SSs that mediate interactions with host membranes 15 . Importantly, recent bioinformatic searches detected related gene clusters in hundreds of diverse bacterial and even archaeal genomes 11 , 15 17 .…”
Section: Mainmentioning
confidence: 99%